2008
DOI: 10.1523/jneurosci.5044-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Rate Code for Sound Azimuth in Monkey Auditory Cortex: Implications for Human Neuroimaging Studies

Abstract: Is sound location represented in the auditory cortex of humans and monkeys? Human neuroimaging experiments have had only mixed success at demonstrating sound location sensitivity in primary auditory cortex. This is in apparent conflict with studies in monkeys and other animals, in which single-unit recording studies have found stronger evidence for spatial sensitivity. Does this apparent discrepancy reflect a difference between humans and animals, or does it reflect differences in the sensitivity of the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
89
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 65 publications
17
89
1
Order By: Relevance
“…In hemifield tuning, neurons exhibit wide tuning curves with a flat maximum corresponding to sound sources either to the left or to the right. This type of tuning is consistent with the neural codes of auditory space found previously in single-unit studies of primate cortex 7 and MEG studies of the human brain 8 utilizing free-field stimuli. Therefore, it seems that in the human cortex the hemifield coding strategy applies to all horizontal sound source localization cues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In hemifield tuning, neurons exhibit wide tuning curves with a flat maximum corresponding to sound sources either to the left or to the right. This type of tuning is consistent with the neural codes of auditory space found previously in single-unit studies of primate cortex 7 and MEG studies of the human brain 8 utilizing free-field stimuli. Therefore, it seems that in the human cortex the hemifield coding strategy applies to all horizontal sound source localization cues.…”
Section: Discussionsupporting
confidence: 90%
“…Neurophysiological evidence for this code has been found in small mammals 5,6 but it is unclear to what extent the results can be generalized to humans. Studies of spatial coding in the monkey 7 and human 8 auditory cortices have found receptive fields consistent with the hemifield code by utilizing free-field sound stimulation. It is, however, not clear what the contribution of ITD is in these results.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, even small differences between sound stimuli led to large differences in the activity level, and this allowed for better discrimination-that is, perceptual expansionat the boundary. A similar association between discriminability and the shape of neuronal tuning curves has been demonstrated in the auditory cortex for the representation of sound source location (Stecker, Harrington, & Middlebrooks, 2005;Werner-Reiss & Groh, 2008). Localization is best for sound sources in frontal directions, although the majority of spatially sensitive neurons in the auditory cortex are maximally tuned to sound sources either to the left or to the right.…”
Section: Discussionsupporting
confidence: 60%
“…There is also evidence from animal studies suggesting ILD neurons in primary auditory cortices, for example, in the cat (50) (note, however, that the link between animal physiology and human fMRI is relatively weak in the spatial auditory domain) (51). Further, our auditory systems are highly adaptive, and different cues may govern distance perception in different acoustic environments.…”
Section: Discussionmentioning
confidence: 99%